A Subset of Nucleus Accumbens Neurons Receiving Dense and Functional Prelimbic Cortical Input Are Required for Cocaine Seeking - Siemsen, Benjamin M.; Barry, Sarah M.; Vollmer, Kelsey M.; Green, Lisa M.; Brock, Ashley G.; Westphal, Annaka M.; King, Raven A.; DeVries, Derek M.; Otis, James M.; Cowan, Christopher W.; Scofield, Michael D. (Frontiers in Cellular Neuroscience, 2022)
Background: Prelimbic cortical projections to the nucleus accumbens core are critical for cue-induced cocaine seeking, but the identity of the accumbens neuron(s) targeted by this projection, and the transient neuroadaptations contributing to relapse within these cells, remain unknown. Methods: Male Sprague-Dawley rats underwent cocaine or sucrose self-administration, extinction, and cue-induced reinstatement. Pathway-specific chemogenetics, patch-clamp electrophysiology, in vivo electrochemistry, and high-resolution confocal microscopy were used to identify and characterize a small population of nucleus accumbens core neurons that receive dense prelimbic cortical input to determine their role in regulating cue-induced cocaine and natural reward seeking. Results: Chemogenetic inhibition of prelimbic cortical projections to the nucleus accumbens core suppressed cue-induced cocaine relapse and normalized real-time cue-evoked increases in accumbens glutamate release to that of sucrose seeking animals. Furthermore, chemogenetic inhibition of the population of nucleus accumbens core neurons receiving the densest prelimbic cortical input suppressed cocaine, but not sucrose seeking. These neurons also underwent morphological plasticity during the peak of cocaine seeking in the form of dendritic spine expansion and increased ensheathment by astroglial processes at large spines. Conclusions: We identified and characterized a unique subpopulation of nucleus accumbens neurons that receive dense prelimbic cortical input. The functional specificity of this subpopulation is underscored by their ability to mediate cue-induced cocaine relapse, but not sucrose seeking. This subset of cells represents a novel target for addiction therapeutics revealed by anterograde targeting to interrogate functional circuits imbedded within a known network.